The Influence of Education Quality Management Strategies and Teachers’ Intrinsic Motivation on Teaching Innovation in Public Elementary Schools in Semendawai Barat - Yesi Ulistina; Bukman Lian; Suherman Suherman (Yayasan Sembilan Pemuda Indonesia, 2027)
This article examines the influence of education quality management strategies and teachers’ intrinsic motivation on teaching innovation in public elementary schools in Semendawai Barat. The study was developed from a quantitative survey conducted in the context of elementary education, where schools are expected to improve learning quality while responding to curriculum change, technology development, and the need for student-centered pedagogy. The research focused on three variables: education quality management strategy as the first independent variable, teachers’ intrinsic motivation as the second independent variable, and teaching innovation as the dependent variable. Data were collected from teacher respondents through questionnaires supported by observation and documentation. The instrument was organized using Likert-scale statements and tested for validity and reliability before being analyzed. Data analysis used prerequisite tests, simple regression, and multiple linear regression. The findings show that education quality management strategies have a positive and significant influence on teaching innovation. Teachers’ intrinsic motivation also has a positive and significant influence on teaching innovation. Simultaneously, both variables contribute significantly to the development of innovative teaching practices. The multiple regression model indicates that the combined contribution of quality management strategies and teachers’ intrinsic motivation explains 29.6% of the variation in teaching innovation, while the remaining proportion is influenced by other factors outside the research model. These findings indicate that teaching innovation cannot be built only through individual creativity or school policy alone. It requires an integrated relationship between systematic quality management, supportive leadership, continuous evaluation, professional development, and teachers’ internal willingness to improve their teaching. The article concludes that the strengthening of school quality management and intrinsic teacher motivation is essential for building sustainable teaching innovation in elementary education.